YBX1 Protects against Apoptosis Induced by Oxygen-Glucose Deprivation/Reoxygenation in PC12 Cells via Activation of the AKT/GSK3β Pathway - Tuerxun, T; Li, X; Lou, F; Wang, X; Ma, L (Folia biologica, 2021)
Reperfusion therapies for ischaemic stroke can induce secondary injury accompanied by neuronal death. The Y-box binding protein 1 (YBX1), an oncoprotein, is critical for regulating tumour cell proliferation and apoptosis. Thus, we wanted to know whether YBX1 could regulate neuronal cell apoptosis caused by cerebral ischaemia/reperfusion (I/R). We established a model of cerebral I/R-induced injury in vitro by oxygen-glucose deprivation/reoxygenation (OGD/R) treatment and determined YBX1 expression using Western blot. Next, the effect of YBX1 on the apoptosis and viability of OGD/R-treated PC12 cells was evaluated by flow cytometry, MTT assay, and Western blot. Besides, the release of lactate dehydrogenase (LDH) and the activity of catalase (CAT) and superoxide dismutase (SOD) were detected to evaluate oxidative stress of PC12 cells induced by OGD/R. The regulatory roles of YBX1 in the AKT/GSK3β pathway were examined by Western blot. As a result, OGD/R treatment down-regulated YBX1 expression in PC12 cells. YBX1 over-expression attenuated the growth inhibition and apoptosis of PC12 cells induced by OGD/R. Besides, the increase of LDH release and the decrease of SOD and CAT activities caused by OGD/R were reversed by YBX1 over-expression. Moreover, YBX1 over-expression could activate the AKT/GSK3β pathway in OGD/ R-treated PC12 cells. Therefore, YBX1 could protect against OGD/R-induced injury in PC12 cells through activating the AKT/GSK3β signalling pathway, and thus YBX1 has the potential to become a therapeutic target for cerebral I/R-induced injury.
Keywords: Cell Survival; Oxidative Stress; ischemie mozku; oxidační stres; Brain Ischemia; DNA-Binding Proteins; PC12 Cells; DNA vazebné proteiny; Stroke; buňky PC12; viabilita buněk; krysa rodu Rattus; zvířata; glukosa; apoptóza; cévní mozková příhoda; Oxygen; protoonkogenní proteiny c-akt; kyslík; kinasa glykogensynthasy 3beta; Proto-Oncogene Proteins c-akt; Glycogen Synthase Kinase 3 beta; Glucose; Reperfusion Injury; Rats; Animals; Apoptosis; reperfuzní poškození